Nanoscience : nanobiotechnology and nanobiology - Boisseau, P. ; Houdy, P. ; Lahmani, M. (Springer, 2020)
Nanobiotechnology is a rapidly developing field of research with new applications constantly emerging. This book presents the basics, fundamental results and latest achievements of nanobiotechnological research. It extends as far as promising applications of new nanomaterials and newly discovered nanoeffects. Additionally, it presents a large variety of nanobio-analysis methods.